Small and Medium-Sized Enterprises and the Financing of Their Development by Bond - Kharbouch Ph.D, Omar; Daoui Ph.D, Driss (International Journal of Engineering and Technology, 2019)
The company has always been concerned about its means of financing in order to ensure its survival and ensure its development. In recent years, and in a context characterized by the crisis, a new means of financing has developed "bond issues", while presenting advantages in terms of cost and risk compared to other bank loans, and especially for small and medium enterprises (SMEs).Â